Amuk Suporter PSIS dalam Narasi Media - Fajar Junaedi (Jurnal ILMU KOMUNIKASI, 2014)
Abstract: The growth of soccer clubs in the cities and districts in Central Java provokes clashes among supporters, and even between supporters and locals. This article looks at how local daily newspapers, Suara Merdeka and Wawasan, built a narrative reports related to the clash by using Marie Gillespieâ€™s narrative analysis model to see the structures. The analysis shows the narratives put fanatic supporters as citizenâ€™s enemy. Interestingly, the narratives also depict fanatic supporters as â€œpowerlessâ€ group who has to be rescued by the army or security forces, whereas in Europe, especially in Italy and the UK, supporters are strictly against themAbstrak: Pertumbuhan klub sepak bola di kota dan kabupaten di Jawa Tengah menyulut bentrokan supporter-suporter dan suporter-warga. Tulisan ini melihat koran Suara Merdeka dan Wawasan membangun narasi pemberitaan mengenai peristiwa tersebut. Metode analisis naratif model Marie Gillespie dipakai untuk melihat rangkaian struktur narasi beritanya. Narasi pemberitaan kedua koran tersebut menempatkan supporter rusuh sebagai musuh warga dan harus diselamatkan polisi dan tentara. Padahal, di Eropa, terutama di Italia dan Inggris, supporter rusuh justru menjadikan aparat keamanan sebagai musuh mereka